Immunogenicity and safety of adjuvant-associated COVID-19 vaccines: A systematic review and meta-analysis of randomized controlled trials - Meng-Qun Cheng; Rong Li; Xin Luo; Jing-Yu Chen; Zhong-Ping Bai; Pin Zhao; Zhi-Ying Weng; Gao Song (Heliyon, 2023)
Background: The benefits and risks of adjuvant-associated COVID-19 vaccines (ACVs) are unclear. The study aimed to assess the immunogenicity and safety of ACVs compared with controls (placebo or the same vaccine without adjuvants [NACVs]). Methods: Randomized controlled trials sourced from PubMed, EMBASE, Web of Science, and Cochrane Library were systematically reviewed. Evaluators extracted information independently. The evidence quality was assessed using random-effects models. The risk of bias was assessed using the Cochrane Risk of Bias tool. Results: Of the 33 studies, 27 analyzed immunogenicity (n = 9069, ACVs group; n = 3757, control), and 26 analyzed safety (n = 58669, ACVs groups; n = 30733 control). Compared with controls, full vaccination with ACVs produced significant immune responses (relative risk [RR] of seroneutralization reaction, 12.3; 95 % confidence interval [95 % CI], 6.92–21.89; standardized mean deviation of geometric mean titer 3.96, 95 % CI, 3.35–4.58). Additionally, ACVs produced significant immunoreactivity compared with NACVs only (P < 0.05). Furthermore, full vaccination with ACVs significantly increased the risk of local and systemic adverse reactions (AEs) compared with controls. However, vaccination with ACVs did not significantly increase the risk of systemic and localized AEs compared with vaccination with NACVs only (P > 0.05). It was observed that ACVs had a lower risk of all-cause mortality than controls (RR, 0.51; 95 % CI 0.30–0.87). It was further found that ACVs produced nAb response against all sublines of the Omicron variant, but the antibody titers were lower than those for the SARS-CoV-2 original strain. Conclusions: The findings of this meta-analysis demonstrate that ACVs may have a superior effect and an acceptable safety in preventing COVID-19. Although these results suggest the potential of ACVs, further studies are required.